Caregiving Across Diverse Populations: New Evidence From the National Study of Caregiving and Hispanic EPESE. Issue 2 (9th September 2019) - Rote, Sunshine M; Angel, Jacqueline L; Moon, Heehyul; Markides, Kyriakos
Abstract: Background and Objectives: The current study employs population-based data to determine the extent to which stress and coping factors are related to self-rated health and distress for informal caregivers (CGs) from the 3 largest racial/ethnic groups in the United States (non-Latino White, African American, and Mexican American). Research Design and Methods: Data on primary, informal CGs are obtained from the 2015 National Study of Caregiving (NSOC) ( n = 667) and the 2016 Hispanic Established Populations for the Epidemiologic Studies of the Elderly (H-EPESE) CG supplement ( n = 287). Logistic regression models of health are presented for all CGs and specifically for dementia CGs. Results: Caregiving intensity is related to health for non-Latino White CGs and African American dementia CGs. Support from family and friends is related to better self-rated health, but only for African American dementia CGs. While better relationship quality is related to better health for African American CGs and White dementia CGs, formal support utilization is related to worse CG health for Mexican American dementia CGs. Discussion and Implications: Findings emphasize the importance of earlier detection and intervention with CGs at the beginning in the caregiving career, the interplay of formal and informal support, and appropriate ways to intervene with dementia CGs. Culturally tailored home- and community-based care options are needed to supplement the low levels of CG support, especially for the Mexican American population.